Factors Affecting Tuberculosis Treatment Adherence among Newly Diagnosed Patients Attending TB Clinic at Tertiary Care Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2024)
Background: Pakistan ranks fifth among high tuberculosis (TB) burden countries. Despite Directly Observed Treatment Short Course Strategy (DOTS) implementation, adherence is still poor and Pakistan stood fourth in multi-drug resistant (MDR-TB) cases. This study was conducted to assess tuberculosis treatment adherence among newly diagnosed pulmonary TB patients at TB clinic of tertiary care hospital, Lahore, and to study factors affecting it.Patients and methods: Between May 2021 and February 2022, cross-sectional study was conducted at outdoor based TB Clinic, Services Hospital, Lahore, interviewing 732 active pulmonary TB patients aged 18 to 65 receiving Anti Tuberculosis Treatment (ATT) for at least two months. Adherence was studied incorporating Morisky Medication Assessment Scale (MMAS) and World Health Organization multi-dimensional adherence model (WHO-MAM) in close-ended questionnaire, considering socio-demographic, patient, health system, and therapy-related factors. Those scoring < 6 on MMAS were categorized low adherents. SPSS Version 25 analysed data. Chi-square test and binary logistic regression explored adherence associations, with p
Keywords: Tuberculosis; Medication Adherence; Morisky Medication Assessment Scale; Factors